Health care experiences of mothers of children with bronchiectasis in Counties Manukau, Auckland, New Zealand - Nicola Jepsen; Nadia A. Charania; Sarah Mooney (BMC, 2018)
Abstract Background Bronchiectasis is a worsening public health problem in New Zealand. This study aimed to explore the health care experiences of mothers of children with bronchiectasis in the Counties Manukau District Health Board area of Auckland, New Zealand. Methods Semi-structured interviews were undertaken with ten mothers of children with bronchiectasis. Data were analysed using thematic analysis. Results Five themes emerged: 1) Searching for answers, describing mothers' search for a diagnosis; 2) (Dis)empowerment, describing mothers' acquisition of knowledge, leading to empowerment; 3) Health care and relationships, describing the impact of relationships on the mother's health care experiences; 4) A juggling act, describing the challenges of juggling health care with school, work and family; 5) Making it work, describing how mothers overcome barriers to access health care for their child. Conclusions The health provider-parent relationship was crucial for fostering positive health care experiences. Mothers' acquisition of knowledge facilitated empowerment within those relationships. Additionally, mothers' perceptions of the quality and benefit of health services motivated them to overcome barriers to accessing care. Study findings may help to improve health care experiences for parents of children with bronchiectasis if identified issues are addressed.